2016
DOI: 10.1371/journal.pone.0156163
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Slow Progressors Show Increased IL-6 and IL-10 Levels in the Pre-AIDS Stage of HIV Infection

Abstract: Cytokines are intrinsically related to disease progression in HIV infection. We evaluated the plasma levels of Th1/Th2/Th17 cytokines in extreme progressors, including slow (SPs) and rapid (RPs) progressors, who were thus classified based on clinical and laboratory follow-up covering a period of time before the initiation of HAART, ranging from 93–136.5 months for SPs and 7.5–16.5 months for RPs. Analyses were also performed based on the different stages of HIV infection (chronic, pre-HAART individuals—subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Contrary to findings of a comparative study that showed that hypertensive immunosuppressed patients had lower IL-10 compared to non-hypertensive immunosuppressed cases [29,30]. The observation in this study was statistically insignificant, P<0.886.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to findings of a comparative study that showed that hypertensive immunosuppressed patients had lower IL-10 compared to non-hypertensive immunosuppressed cases [29,30]. The observation in this study was statistically insignificant, P<0.886.…”
Section: Discussioncontrasting
confidence: 99%
“…Although there is no consensus on "biomarkers" of systemic immune activation, elevation of sCD14 has been shown to be a relatively sensitive marker for predicting HIV progression (Williams, Livak, Bahk, Keating, & Adeyemi, 2016). Other markers, such as TNF-α, have more controversial roles (de Medeiros et al, 2016;Vaidya et al, 2014). The association for sCD14 among PHIV but not PHEU underscore the potential risk of HIV progression.…”
Section: Discussionmentioning
confidence: 99%
“…Altered T cell homeostasis in the gut, particularly of CD4 + Th17 cells, coincides with disruption of intestinal barrier function, in which the tightly opposed enterocytes become “leaky” and lose their adherence to adjacent cells (Dandekar et al, 2010). Reports of increased and dysregulated IL-10 production in SIV and HIV infection have also been linked to intestinal permeability and inflammatory signatures (Pan et al, 2014; de Medeiros et al, 2016). Intestinal barrier disruption leads to translocation of microbial products from the lumen to systemic circulation, traveling to far-reaching organs such as the liver and brain and inducing persistent immune activation (Brenchley et al, 2006; Estes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%